Betting one's life on the future of print - Cousins, Norman; American Library Association. Conference (91st). (Los Angeles, Calif. CREDR Corp., 1973)
So long as there is a human mind that needs nourishment, there will be print. There is nothing in the world that kindles the imagination more than a book
American library association, 91st annual conference. Media: man, material, machine.
Keywords: Books and reading -- Congresses; Library science